Pelatihan Pembuatan Nata de coco di Perkebunan Kelapa Desa Margomulyo Kecamatan Seyegan Kabupaten Sleman - Wiwit Probowati; Aulia Ulfah Mu’awanah (Jurnal Pengabdian Masyarakat MIPA dan Pendidikan MIPA, 2021)
Coconut plants are very potential commodities, all parts of the coconut plant are beneficial to the needs of human life. All parts of coconuts are not wasted and can be used to produce industrial products. The partners are coconut farmers who sell peeled coconut and coconut flesh. Farmers in Margomulyo village have difficulty in handling the waste of untreated coconut water. Sometimes the coconut water causes inundated land without being used. Sometimes when the coconut water is not directly absorbed in the ground, it will cause bad odor in the environment. Therefore, the use of coconut water is a way to optimize the use of coconut fruit. The content of sucrose sugar in coconut water will be used by Acetobacter xylinum as a source of energy, as well as a carbon source to form metabolite compounds such as cellulose that form Nata de Coco. In conclusion, Nata de coco making training in Margomulyo village gave positive response for the community to establish business unit. The barrier to the implementation of this activity was that there was no solution for handling waste production of Nata de coco of which aroma was quite disturbing. Thus, the implementation of nata de coco waste treatment program will be overcomed in further implementation of community service program which will be held in the next period